Peningkatan Hasil Belajar IPA dengan Media Belajar Midi Webcam pada Sekolah Menengah Pertama - Ibnu Dwi Kustadiyono (Jurnal LENTERA: Jurnal Studi Pendidikan, 2022)
The purpose of this study is to improve IPA learning outcomes in students with Midi Webcam learning media that have the characteristics of providing stimulus or stimulation, hypothesis submission, data collection, and presentation. Class Action Research is carried out in two cycles and each cycle consists of action planning, action execution, observation, and reflection. The subjects in this study were 26 students of class VII-1 SMP Negeri 1 Taliwang with teaching materials of The Organization of Life System. Research instruments in the form of teacher observation sheets, student observation sheets, and evaluation tests were used in this study to collect data. Research results data are analyzed descriptively to determine the implementation of learning and improvement of student learning outcomes. The results showed improvements in students' learning outcomes after being given action on each implementation cycle in the study. Based on the results of research it can be concluded that learning with Midi Webcam media can improve student learning outcomes.